2016
DOI: 10.33230/jps.4.2.2015.2805
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Serat Kasar, Lemak Kasar, dan BETN terhadap Lama Penyimpanan Wafer Rumput Kumpai Minyak dengan Perekat Karaginan

Abstract: Tujuan penelitian ini adalah untuk  mengetahui kualitas serat kasar, lemak kasar dan BETN terhadap lama penyimpanan wafer rumput kumpai minyak dengan  perekat karaginan. Penelitian ini dilaksanakan di Laboratorium Nutrisi dan Makanan Ternak Program Studi Peternakan, Fakultas Pertanian, Universitas Sriwijaya selama 2 bulan dari bulan November sampai Desember 2014.  Penelitian ini menggunakan Rancangan Acak Lengkap yang terdiri dari 4 perlakuan dan 5 ulangan. R1 (wafer rumput kumpai minyak dengan perekat kara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
2
3
0
6
Order By: Relevance
“…The nutritional value of crude fiber for P1, P2 and P3 was inversely proportional to that of TDN and NFE. This result is consistent with that of Sari et al (2015), who showed that decreases in crude fiber content of feed material are associated with increased NFE content.…”
Section: Chemical Composition Of Haysupporting
confidence: 92%
“…The nutritional value of crude fiber for P1, P2 and P3 was inversely proportional to that of TDN and NFE. This result is consistent with that of Sari et al (2015), who showed that decreases in crude fiber content of feed material are associated with increased NFE content.…”
Section: Chemical Composition Of Haysupporting
confidence: 92%
“…The average nitrogen content of 2.70% is related to crude protein content (ranging from 2.70 x 6.25 = 16, 87%). This is higher than the crude protein content of Kumpai grass (Sari, Ali, Sandi, & Yolanda, 2015) which is only 7.99% and the crude protein content of grass growing under oil palm plants ranging from 8-10.5% (Daru, Yuianti, & Widodo, 2013). Meanwhile, the crude protein content of Calopogonium mucunoides ranges from 2-4% (Prawiradiputra, Sutedi, Sajimin, & Fanindi, 2012), and of green leaved rice is 8-14% (Jamilah, Juniarti, & Srimulyani, 2016).…”
Section: Resultsmentioning
confidence: 92%
“…(Styawati et al, 2014) Crude fiber content decreases with increasing fermentation time. (Sari et al 2015) reduction of crude fiber during storage is due to microorganisms' breakdown activity on lignocellulose from the crude fiber. (Lamid et al 2013) It caused the cellulase enzyme produced work at seven days has loosened the α-1,4-glycosidic bonds in the cellulose components.…”
Section: Resultsmentioning
confidence: 99%